Law No. 12 of the year 2017 Amending Certain Provisionsof Law No. 162 of the year 1958 On the State of Emergency = قانون رقم 12 لسنة 2017 بشأن تعديل بعض أحكام القانون رقم 162 لسنة 1958 فى شأن حالة الطوارئ - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic